Monetary Policy Pass-through, Ownership and Crisis: How Robust is the Indian Evidence?. (November 2021) - Ansari, Jugnu; Ghosh, Saibal
Employing disaggregated data for 2001–2016, this study investigates the lending and loan pricing behaviour of state-owned and domestic private banks in response to monetary policy. Three major findings emerge. First, although both the interest rate and the bank lending channels are relevant for monetary pass-through, there is a trade-off: the impact of the former is much higher than the latter, although it occurs with a significant lag. Second, domestic private banks have a far greater response to a monetary policy shock under the interest rate channel, whereas state-owned banks display a greater response under the bank-lending channel. And finally, state-owned banks cut back lending during periods of crises, although no such response is manifest in domestic private banks. JEL Codes: C23, D4, E43, E52, G21, L10